Yeast proteins originated from the production of brazilian bioethanol quantification and content - Steckelberg, Claudia; Da Graça Stupiello Andrietta, Maria; Andrietta, Silvio Roberto; Stupiello, Erika Nogueira Andrade [UNESP] (De Gruyter, 2013)
The purpose of this work was to determine the levels of protein and the amino acid distribution in the cell mass of yeast strains (Saccharomyces sensu stricto) originated from Brazilian bioethanol industries. The protein was analyzed with the Kjeldahl method and the amino acids, by using high-performance liquid chromatography (HPLC). The percentages of the protein found ranged from 39 to 49%. The results show that in spite of some variation in numbers between the different yeast strains, all of them presented an amino acid profile similar to the one in the literature for S. cerevisae. The amino acids that have occurred in the largest amounts were: aspartic, glutamic acids and lysine, and those in the lowest amounts were: cysteine and methionine. Although the characteristics of the feedstock used and the process conditions are determinant of the protein values obtained in dry mass, this work elucidates that the intrinsic properties of the yeast strain influence these values.
Keywords: Amino acids; Bioethanol; Biofuel production; Saccharomyces sensu stricto; Single cell protein; Acid distribution; Bioethanol industry; Intrinsic property; Kjeldahl methods; Process condition; Saccharomyces; Single cell proteins; Ethanol; High performance liquid chromatography; Proteins; Strain; Yeast